2022
DOI: 10.3390/brainsci12101352
|View full text |Cite
|
Sign up to set email alerts
|

Declarative Memory Impairment and Emotional Bias in Recurrent Depression with a Seasonal Pattern: The Interplay between Emotion and Cognition in Seasonal Affective Disorder

Abstract: Seasonal Affective Disorder (SAD) is a subtype of Major Depressive Disorder (MDD) with a seasonal pattern. Although it is a pathological condition limited to specific seasons of the year, during the symptomatic period, patients may experience a significant impairment of well-being and daily quality of life as a result of the depressed mood, associated with other symptoms defined as atypical of MDD. While extensive evidence of memory deficits has been found in MDD, explicit memory impairments in SAD are insuffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 65 publications
1
4
1
Order By: Relevance
“…We may speculate that there is a tendency for enhanced processing of negative stimuli, leading to better recognition performance in individuals with elevated seasonality scores. This is in contrast with previous research that reported lower overall recognition memory in individuals with winter depression during the symptomatic phase [30]. This divergence in results might be explained by at least two differences between the present work and prior studies.…”
Section: Behavioral Results: Emotional Biases Independent Of Seasonalitycontrasting
confidence: 99%
See 2 more Smart Citations
“…We may speculate that there is a tendency for enhanced processing of negative stimuli, leading to better recognition performance in individuals with elevated seasonality scores. This is in contrast with previous research that reported lower overall recognition memory in individuals with winter depression during the symptomatic phase [30]. This divergence in results might be explained by at least two differences between the present work and prior studies.…”
Section: Behavioral Results: Emotional Biases Independent Of Seasonalitycontrasting
confidence: 99%
“…This divergence in results might be explained by at least two differences between the present work and prior studies. Firstly, prior research [30,33] was based on data that were collected during winter, as opposed to summer in our study. Secondly, also the stimulus material differed.…”
Section: Behavioral Results: Emotional Biases Independent Of Seasonalitymentioning
confidence: 99%
See 1 more Smart Citation
“…They include memory impairment, lack of wellbeing, psychological morbidity, depression, and sleep problems, all of which are notably comorbid. In one of the rare experimental studies comparing adults with SAD and adults without SAD (N=120), neutral or arousal stimuli were presented [10]. The researchers reported that both attention bias to negative stimuli and declarative memory impairment occurred in those with SAD on recall and recognition tasks.…”
Section: Effects Of Seasonal Affective Disordermentioning
confidence: 99%
“…Memory is one of the most important cognitive factors that is affected by depression and is associated with serious deficiencies due to depression (Nafilyan et al, 2021). Depressed people face reduced cognitive performance, major problems in everyday situations (forgetting names and misinterpreting directions), and defects in controlled processes such as attention and working memory (Iorio et al, 2022). In the study of (Vancappel et al, 2021), it is stated that persistent depression disorders can have a strong effect on memory loss, so in the tests conducted, people showed a significant difference in memory tests before and after suffering from depression.…”
Section: Introductionmentioning
confidence: 99%